M.O.M. Mother of Madness - Clarke, Emilia 1986-; Bennett, Marguerite 1988- (Image Comics, 2021)
The mayhem begins with Maya, under-the-weather scientist by day, over-the-top superhero by night, and badass single mom 24/7. Deadpool action and Fleabag comedy collide when Maya activates her freakish superpowers to take on a secret sect of human traffickers. Bath time's at 7pm, bedtime's at 8pm, and crimefighting never sleeps when villains out of Maya's shadowy past come to collect
Collects the complete limited series, M.O.M.: MOTHER OF MADNESS #1 - #3
Keywords: Scientists -- Comic books, strips, etc; Scientists -- Fiction; Mothers -- Comic books, strips, etc; Mothers -- Fiction; Superheroes -- Comic books, strips, etc; Bekämpfung; Alleinerziehende Mutter; Wissenschaftlerin; Menschenhandel; Kriminalität; Superheldin; Science fiction comic books, strips, etc; Fiction; Comic; Superhero comics; Science fiction comics; Graphic novels; Comics (Graphic works)